Climate Change Adaptation and Mitigations: Students’ Knowledge and Experiences in Jimma University, Ethiopia - Gemeda, Dessalegn Obsi; Sima, Akalu Dafisa (2015)
Climate change adaptation and mitigation are essential to minimize the potential impacts of climate particularly for the Sub-Saharan Africa like Ethiopia due to high vulnerability to the effects of climate change. Afforestation, re-afforestation, forest conservation, using water in efficient way, water harvesting and storage techniques, livelihood diversifications and green economy are some of the potential climate change adaptation and mitigation options. The study was conducted in Jimma University College of Agriculture and Veterinary Medicine to assess the student knowledge and experiences on climate change adaptation and mitigation strategies and the way forward to minimize the future impacts of climate change. A total of 95 respondents were purposively selected from the Department of Natural Resources Management and Agricultural Economics and Extensions. Open and close ended questionnaire were distributed to the students in the classroom at the end of the semester for data collection. The collected data were analyzed by using Microsoft office excel and Statistical Pakage for Social Science version 20. Descriptive Statistics such as frequency and percentage were employed to examine the student knowledge and experiences on adaptation and mitigation options. The results of the study show that majority of the students (87.4%) perceived that climate change is occurring in Ethiopia. Based on their knowledge and experiences on climate change and its impacts the students prioritized afforestation, forest conservation, re-afforestation, wise use of water and diversifying community livelihoods as the top five ranked adaption and mitigation options in Ethiopia. The study suggests that capacity building at different levels in the form of training and workshop on climate change adaptation and mitigation is crucial; the wise use of natural resources in general and specifically the conservation of forest should be encouraged in all regions of Ethiopia and the Ethiopian Ministry of Education should incorporate the issue of climate change and its adaptation and mitigation options in all discipline as much as possible.
openalex:W1556513959 mag:1556513959 KerkoCite.ItemAlsoKnownAs: 5072953:XK22EBWH
Keywords: C:Ethiopia; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:topic:T10119 Sustainability Transitions and Resilience in Social-Ecological Systems; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found